Speed under sail, 1750-1830 - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2017)
We measure technological progress in oceanic shipping directly by using a large database of daily log entries from ships of the British and Dutch East India Companies and Navies to estimate daily sailing speed in different wind conditions from 1750 to 1850. Against the consensus among economic (but not maritime) historians that the technology of sailing shipswas static during this time, we find that average sailing speeds of British ships in moderate to strong winds rose by nearly a third. Driving this steady progress seems to be continuous evolution of sails and rigging, and improved hulls that allowed a greater area of sail to be set safely in a given wind. By contrast, looking at every voyage between the Netherlands and East Indies undertaken by the Dutch East India Company from 1595 to 1795, we find that journey time fell only by 10 per cent, with no improvement in the heavy mortality, averaging six per cent per voyage, of those aboard.
Keywords: N0; 330; Technological progress; shipping